Ukraine after the crisis: Recovery and reform, not revolution or Russification - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2010)
This Policy Brief aims at examining Ukraine's economic woes and what it needs to do to improve economic performance. At the centre of the Brief are the effects on Ukraine of the economic crisis and the policy programme devised to improve economic performance. The crisis hit Ukraine hard and Gross Domestic Product fell by 15 percent in 2009. The economy is now recovering, but economic growth will not return to pre-crisis levels anytime soon. Ukraine went through a classic emerging-market crisis - it was too dependent on export of steel and metals, and it was too exposed to adverse development on international credit markets. The reform agenda set out by the new Ukrainian government is ambitious. If the government delivers on its promises - and obligations to the International Monetary Fund - economic policy will move in a liberal direction and economic growth is likely to pick up. There are hesitations about the ability to push through all reforms, but the Ukrainian government has been forced to tie itself to the IMF mast and should make full use of this opportunity to liberalize economic policy and modernize the economy. There are also hesitations based on President Yanukovych and his political orientation towards Russia. Sceptics may or may not be proven right - it is too soon to tell. What seems clear, however, is that Ukraine favours a much more pragmatic approach to its neighbors in the east and the west. It is not difficult to understand why. Ukraine's relations to Russia had to improve and as long as the EU does not wish to start the process for full accession, Ukraine needs to find its own way and build a reform and future agenda on other foundations.
Keywords: 330; Finanzkrise; Wirtschaftspolitik; Außenwirtschaftspolitik; Wirtschaftsreform; Politische Reform; Ukraine